The Reliability and Validity of Adolescent Health Promotion Scale in Turkish Community Original Article - Ayla Bayık Temel; Fatma Başalan İz; Sema Yıldız; Derya Yetim (Güncel Pediatri)
Introduction: Health-promoting lifestyles of adolescents are closely related to their current and subsequent health status. However, few studies in Turkey have examined health-promoting behaviors of adolescents. The purpose of this study was to examine the reliability and validity of Adolescent Health Promotion Scale that was translated into the Turkish language.Materials and Method: In study, item analysis, exploratory factor analysis, and reliability measures of the scale, were assessed based on the responses of 358 students. Results: Factor analysis yielded a six-factor instrument that explained 38.48% of the variance in the 40 items. The Cronbach’s alpha reliability coefficient for the total scale was calculated 0.86, and ranged from 0.50 to 0.74 for the subscales. Conclusion: The results indicated that the Turkish version of the Adolescent Health Promotion Scale is a reliable and valid tool for use among Turkish students. (Journal of Current Pediatrics 2011; 9: 14-22)